Uji aktivitas antioksidan ekstrak etanol daun benalu Helixanthera cylindrica (Jack) Danser pada tumbuhan kelor (Moringa oleifera) dengan metode 2,2-diphenyl-1-picrylhydrazyl - Potalangi, Nerni Olvi; Palandi, Reky Royke; Manoppo, Amalia J.; Tewu, Tewsi M.; Kanter, Jabes Wolter; Sambou, Christel Nataniel (Journal of Pharmaceutical and Sciences, 2024)
Free radicals can originate from within the human body as a result of metabolic processes from chemical reactions in the body, as well as from external sources or the environment, including emissions from motor vehicles, air pollution from factories, industrial chemicals, food and beverage substances, cigarette smoke, radiation, and sunlight. Antioxidants are components that can prevent cells or molecules from being oxidised by donating electrons or hydrogen atoms to free radicals. The impact of the reactivity of free radical compounds can result in cell or tissue damage, degenerative diseases, and even cancer. One of the parasites on the moringa plant, namely Helixanthera cylindrica (Jack) Danser, contains secondary metabolite compounds such as alkaloids, flavonoids, and saponins. This research aimed to determine whether the leaves of the Helixanthera cylindrica (Jack) Danser mistletoe have antioxidant activity using the 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) method. The research method is a laboratory experiment with five concentrations and three repetitions. Subsequently, the antioxidant activity testing is conducted qualitatively using the DPPH method at a wavelength of 517 nm and utilising a Spectrophotometer UV-Vis. Based on the results of the antioxidant test, the extract of Helixanthera cylindrica (Jack) Danser leaves has extreme activity with an IC50 value of 28.74 ppm. In contrast, the comparison, vitamin C has an IC50 value of 1.57 ppm. The regression equation for the concentration of the mistletoe is y=0.3344x + 40.389 with an R2 value of 0.9726, and Vitamin C shows y=4.4065x + 43.079 with an R² value of 0.9677. It can be concluded that the leaves of Helixanthera cylindrica (Jack) Danser on the Moringa oleifera plant have extreme antioxidant activity.